STUDENTS’ MOTIVATION IN WRITING ANALYTICAL EXPOSITION TEXT THROUGH SCRATCH PROGRAM FOR ELEVENTH GRADE OF SMK BINA BERSAUDARA MEDAN - Maya Devi Purba; Safrida Lubis; Lidiman Sahat Martua Sinaga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This research is to explore the students’ motivation in learning English. Student who has high motivation would do the best in learning even though the materials were felt difficult. The aims of this research is to identify the factor that influence students’ intrinsic and extrinsic motivation and students’ motivation levels in writing analytical exposition text through Scratch Program. This research was conducted by using descriptive qualitative nature. The researcher presented eight items of interview and twenty items of questionnaire. The participants of the research were fifteen students at eleventh grade administration class in SMK Bina Bersaudara Medan. The data were obtained through interview and questionnaires to the students related to their motivation in learning writing text. The findings of this research were found that ten students have the intrinsic motivation and five students have the extrinsic motivation. To decide students in to intrinsic and extrinsic motivation, there are the factors that determine types of students’ motivation in eleventh grade of SMK Bina Bersaudara. First factor of intrinsic motivation were 1) self-desire, 2) Satisfaction, 3) Challenge/Competition, and 4) Good Habit. Seconds the factors of extrinsic motivation were 1) teacher, Parent, and Environment, 2) Reward, and 3) Punishment. In summary, students in eleventh grade of SMK Bina Bersaudara mostly have the dominant motivation of intrinsic than extrinsic motivation. Then, the result discussed about the level of students’ motivation, it was found that the students’ level of motivation is high (4.4). Therefore, it can be concluded that the students’ motivation in learning English in writing analytical exposition text through Scratch Program were in high category.Keywords: Students’ Motivation; Intrinsic Motivation; Extrinsic Motivation; Level of Motivation; Scratch Program.